Ethnography and Modern Languages. Issue 1 (7th January 2019) - Wells, Naomi; Forsdick, Charles; Bradley, Jessica; Burdett, Charles; Burns, Jennifer; Demossier, Marion; de Zárate, Margaret Hills; Huc-Hepher, Saskia; Jordan, Shirley; Pitman, Thea; Wall, Georgia
While rarely explicitly recognized in our disciplinary frameworks, the openness and curiosity on which Modern Languages in the UK is founded are, in many ways, ethnographic impulses. Ethnographic theories and practices can be transformative in relation to the undergraduate curriculum, providing an unparalleled model for experiential and holistic approaches to language and cultural learning. As a form of emplaced and embodied knowledge production, ethnography promotes greater reflexivity on our geographical and historical locations as researchers, and on the languages and cultures through which we engage. An ethnographic sensitivity encourages an openness to less hierarchical and hegemonic forms of knowledge, particularly when consciously seeking to invert the traditional colonial ethnographic project and envision instead more participatory and collaborative models of engagement. Modern Languages scholars are at the same time ideally placed to challenge a monolingual mindset and an insensitivity to language-related questions in existing ethnographic research located in cognate disciplines. For Modern Languages to embrace ethnography with credibility, we propose a series of recommendations to mobilize these new research and professional agendas.1